PENGARUH PEMAHAMAN PERATURAN PAJAK, PELAYANAN FISKUS, PERSEPSI EFEKTIVITAS SISTEM PERPAJAKAN TERHADAP KEMAUAN MEMBAYAR PAJAK (Studi Empiris Pada Kantor Pelayanan Pajak Pratama Jayapura) - Rachmad Putra Ramadhan; Syaikhul Falah; Mariolin Sanggenafa (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2019)
This study aims to analyze and provide empirical evidence of the influence of independent variables, namely the understanding of tax regulations, tax services, and perceptions of the effectiveness of thetax system on the dependent variable of willingness to pay personal taxpayer in Jayapura City. Sampling method was used in this study is nonprobability sampling method with purposive sampling technique (intentional sampling) to determine the desired on target respondents. Respondents who are sampled in this study are taxpayers of individuals registered and classified as effective taxpayers in KPP Pratama Jayapura totaling 100 people. Data analysis was used multiple linear regressionanalysis with SPSS 16.0 application. The result of this research shows that the variable of understanding of tax regulation does not affect the willingness of paying tax, the perception of tax system effectiveness does not affect the willingness to pay the tax, then the tax service variable affect the willingness to pay taxes